Relationship between Organizational Learning and Supply Chain Agility on Organizational Performance: A Quantitative Study in Fashion SMEs - Parama Kartika Dewa; Irma Nur Afiah; Rofiqul Umam (Jurnal Optimasi Sistem Industri, 2024)
Supply Chain Agility (SCA) is recognized as a crucial component in fostering organizational agility, offering a competitive and expansionary strategy for businesses. However, the impact of SCA on organizational performance, particularly in the fashion industry, remains underexplored. This study aims to investigate how learning and agility within the supply chain affect the performance of fashion SMEs, providing a comprehensive understanding of these dynamics. Employing a quantitative approach, data were collected through a questionnaire from 180 fashion SMEs in the Special Region of Yogyakarta, with responses obtained from managers in the fashion industry sector. This methodological choice ensures that the insights gathered are both relevant and specific to the targeted industry. A Structural Equation Modeling using Partial Least Squares (SEM-PLS) was utilized to test the hypotheses, focusing on both the direct and indirect effects of internal and external learning dimensions on organizational performance. The findings reveal that both learning and supply chain agility significantly enhance the performance of fashion SMEs, underscoring their importance in boosting organizational effectiveness. Specifically, the study highlights that internal learning processes and external knowledge acquisition are both critical in fostering a more agile and responsive supply chain. These results contribute to the understanding of how SMEs in the fashion sector can leverage learning and agility to improve performance, supporting the development of more effective supply chain strategies. Consequently, the study's hypotheses are validated, providing valuable insights for practitioners and researchers in the field. This research underscores the potential for fashion SMEs to enhance their competitive edge and operational efficiency through strategic learning and agile supply chain management.